Staphylococcus aureus Quorum Regulator SarA Targeted Compound, 2-[(Methylamino)methyl]phenol Inhibits Biofilm and Down-Regulates Virulence Genes - Balamurugan, P.; Praveen Krishna, V.; Bharath, D.; Lavanya, Raajaraam; Vairaprakash, Pothiappan; Adline Princy, S. (Frontiers in Microbiology, 2017)
Staphylococcus aureus is a widely acknowledged Gram-positive pathogen for forming biofilm and virulence gene expressions by quorum sensing (QS), a cell to cell communication process. The quorum regulator SarA of S. aureus up regulates the expression of many virulence factors including biofilm formation to mediate pathogenesis and evasion of the host immune system in the late phases of growth. Thus, inhibiting the production or blocking SarA protein might influence the down regulation of biofilm and virulence factors. In this context, here we have synthesized 2-[(Methylamino)methyl]phenol, which was specifically targeted towards the quorum regulator SarA through in silico approach in our previous study. The molecule has been evaluated in vitro to validate its antibiofilm activity against clinical S. aureus strains. In addition, antivirulent properties of the inhibitor were confirmed with the observation of a significant reduction in the expression of representative virulence genes like fnbA, hla and hld that are governed under S. aureus quorum sensing. Interestingly, the SarA targeted inhibitor showed negligible antimicrobial activity and markedly reduced the minimum inhibitory concentration of conventional antibiotics when used in combination making it a more attractive lead for further clinical tests.